2003
DOI: 10.1080/16506070310003648
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder Symptoms in United Nations Peacekeepers: An Examination of Factor Structure in Peacekeepers with and without Chronic Pain

Abstract: Recent factor analytic investigations of post-traumatic stress disorder in military veterans suggest that symptoms are best described by either a hierarchical 2-factor model or a 4-factor inter-correlated model. Other recent evidence suggests that post-traumatic stress disorder and chronic pain are intricately related; however, the nature of this relationship is not well understood. Factor analysis provides one method for clarifying this relationship. In study 1, we compared competing models of post-traumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
66
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 30 publications
11
66
0
1
Order By: Relevance
“…Only on the mean scale scores of C symptom cluster (including avoidance symptoms), PTSD patients did not significantly differ from depressive patients. Some of the prior studies suggested that avoidance and numbing symptoms should be conceived as distinct rather than as similar [42,43]. However, contrarily, the four-factor numbing model of PTSD suggested by King et al [16] centres on avoidance and numbing symptoms in their conceptualization.…”
Section: Resultsmentioning
confidence: 99%
“…Only on the mean scale scores of C symptom cluster (including avoidance symptoms), PTSD patients did not significantly differ from depressive patients. Some of the prior studies suggested that avoidance and numbing symptoms should be conceived as distinct rather than as similar [42,43]. However, contrarily, the four-factor numbing model of PTSD suggested by King et al [16] centres on avoidance and numbing symptoms in their conceptualization.…”
Section: Resultsmentioning
confidence: 99%
“…A four-factor, intercorrelated solution, with factors described as re-experiencing, effortful avoidance, emotional numbing, and hyperarousal, provided the best fit. This model has subsequently been supported in several other trauma groups (Asmundson et al, 2003;DuHamel et al, 2004;Marshall, 2004;Palmieri & Fitzgerald, 2005; Palmieri, Marshall, et al, 2007; Palmieri, Weathers, et al, 2007;Stewart et al, 2004). Simms et al (2002) examined the fit of six symptom models in a large group of military personnel (N = 3695).…”
mentioning
confidence: 99%
“…To date, exploratory factor analyses of DSM-III-R/DSM-IV PTSD symptoms have been conducted with numerous populations, including survivors of fires, motor vehicle accidents and assaults, United Nations peacekeepers, refugees, and military veterans (Fawzi et al, 1997;Foa, Riggs, & Gershuny, 1995;Keane, 1993;Maes et al, 1998aMaes et al, , 1998bSack, Seeley, & Clarke, 1997;Shelby, Golden-Kreutz, & Andersen, 2005;Smith, Redd, DuHamel, Vickberg, & Ricketts, 1999;Smith, Perrin, Dyregrov, & Yule, 2003;Stewart et al, 1999;Taylor, Kuch, Koch, Crockett, & Passey, 1998). Two-, three-, four-, and five-factor solutions have been reported, with no solution clearly paralleling the symptom clusters suggested by the most recent versions of the DSM.Along with these exploratory factor analyses, numerous confirmatory factor analyses (CFAs) of DSM-III-R/DSM-IV PTSD symptoms have been conducted (Andrews, Joseph, Shevlin, & Troop, 2006;Anthony, Lonigan, & Hecht, 1999;Anthony et al, 2005;Asmundson et al, 2000;Asmundson, Wright, McCreary, & Pedlar, 2003;Baschnagel, O'Connor, Colder, & Hawk, 2005;Buckley, Blanchard, & Hickling, 1998;Cordova, Studts, Hann, Jacobsen, & Andrykowski, 2000;DuHamel et al, 2004;King, Leskin, King, & Weathers, 1998;Maes et al, 1998aMaes et al, , 1998bMarshall, 2004;McWilliams, Cox, & Asmundson, 2005;Palmieri & Fitzgerald, 2005; Palmieri, Marshall, & Schell, 2007; Palmieri, Weathers, Difede, & King, 2007;Sack et al, 1997;Simms, Watson, & Doebbeling, 2002;Stewart et al, 2004). CFAs have several advantages over exploratory factor analyses in elucidating the structure of PTSD symptoms.…”
mentioning
confidence: 99%
See 2 more Smart Citations